Thrombotic thrombocytopenic purpura relapse induced by acute hepatitis E transmitted by cryosupernatant plasma and successfully controlled with ribavirin. Issue 11 (4th October 2018) - Riveiro‐Barciela, Mar; Bes, Marta; Quer, Josep; Valcarcel, David; Piriz, Sofia; Gregori, Josep; Llorens, Meritxell; Salcedo, María‐Teresa; Piron, Maria; Esteban, Rafael; Buti, Maria; Sauleda, Silvia
Abstract : BACKGROUND: Hepatitis E virus (HEV) can be transmitted by transfusion of any type of blood component, but there are few data on the potential risk of transmitting this virus and the associated complications. We provide evidence that HEV can be transmitted by cryosupernatant plasma, and that HEV infection can act as a trigger for thrombotic thrombocytopenic purpura (TTP). STUDY DESIGN AND METHODS: A patient with a history of TTP treated with plasmapheresis 2 months previously developed jaundice and a TTP exacerbation with purpura, thrombocytopenia, schistocytes, and undetectable ADAMTS‐13 activity. He was diagnosed with acute hepatitis E and treated with ribavirin. TTP remitted with remission of HEV infection. RESULTS: Traceback to determine the source of the infection showed that 1 cryosupernatant plasma among the 99 different blood components used for the patient's last plasmapheresis was positive for HEV RNA, with an estimated viral load of 5000 to 10, 000 IU/mL. Phylogenetic analysis proved the transfusion‐transmitted route of acute hepatitis E. CONCLUSION: In a patient with TTP, acute HEV infection transmitted by cryosupernatant plasma may trigger exacerbation of TTP, which can be controlled on remission of HEV infection with ribavirin.